DEVELOPMENT OF FLAT-BUILT DIGITAL COMIC MEDIA BASED ON ETHNOPEDAGOGY TO IMPROVE THE MATHEMATICAL CONNECTIONS OF LOWER CLASS PRIMARY SCHOOL STUDENTS - Nurafiah Rizkiyani; Iva Sarifah; Faisal Mdani (Universitas Majalengka, 2024)
Meaningful and enjoyable learning is a strategy developed by teachers to optimize learning objectives. This strategy encompasses various aspects, including the approach used, material delivery, engaging instructional media, and creating a pleasant learning environment (Tisza & Markopoulos, 2021). The research was conducted using the Research and Development (R&D) approach, commonly known as development research that results in a product. The purpose of this study was to develop a digital comic-based flat geometry learning media grounded in ethno-pedagogy to enhance elementary school students’ mathematical connections in lower grades. The ADDIE model, developed by Dick and Carey in 1996, was employed as the framework for designing the instructional system (Mulyanitiningsih, 2016).The research outcomes, based on expert validation and field testing, indicate that the digital comic-based flat geometry learning media grounded in ethno-pedagogy aligns well with usability, appropriateness, accuracy, and suitability. The expert validation resulted in an 86% score, with an average material expert score of 96%, categorized as ‘Highly Suitable.’ Additionally, the language experts provided an average score of 82.5%, categorized as ‘Suitable.’ Overall, the combined scores from the experts yielded an 88.16% rating of ‘Highly Suitable’ for use with elementary school students. Based on the effectiveness test, the digital comic-based flat geometry learning media grounded in ethno-pedagogy demonstrated a positive impact on mathematical connections. The N-Gain calculation resulted in an average N-Gain score of 0.7061, categorized as